Erratum to ‘Role of nanotechnology in neurosurgery: A review of recent advances and their applications’ [World Neurosurgery: X (22C) (2024)100298)] - Javed Iqbal; Evan Courville; Syed Faraz Kazim; Michael Kogan; Meic H. Schmidt; Christian A. Bowers (World Neurosurgery: X)
The use of nanotechnology in medicine and healthcare is known as nanomedicine. These nanoparticles exhibit significant potential in medicine, including in imaging techniques and diagnostic tools, tissue-engineered constructs, drug delivery systems, pharmaceutical therapeutics, and implants. The association with neurosurgery had been less well established compared to other organ systems but has recently offered the promising future potential for a wide range of utilities, including CNS drug delivery, neuro-regeneration, neuro oncology, neuroimaging, and neuromodulation. This review summarizes the current developments in nanotechnology and nanomedicine that may yield future neurosurgery applications. A literature review was carried out with a focus on the use of nanotechnology and nanoparticles in the field of neurosurgery and its future implications. Although most therapeutic strategies involving nanotechnology discussed are still in an early experimental stage, it is expected that research on such frontline field will bring a major impact in several neurosurgical areas, opening new opportunities for the treatment of CNS neoplasms, neurodegenerative processes as well as vascular and traumatic injuries.